(400) Labour Productivity in Planning - فريد م. بدران (معهد التخطيط القومى, 2026)
ملخص تتناول هذه المذكرة البحثية الصادرة عن معهد التخطيط القومي عام ١٩٦٤ المبادئ الأساسية للحواسب الرقمية وكيفية التعامل مع المعلومات، حيث تبدأ باستعراض تاريخي لتطور القدرة البشرية على الحساب من العصور القديمة وصولاً إلى ابتكار الأرقام العربية والصفر، ثم تنتقل لتوضيح الفرق بين الحواسب الرقمية التي تعتمد على القيم المنفصلة والمنطق الثنائي (٠ و١) والحواسب القياسية. وتركز المذكرة على البنية الهيكلية للحاسب المكونة من خمس وحدات رئيسية هي الإدخال والتخزين والتحكم والحساب والمخرجات، مع شرح مفصل لكيفية تحويل المسائل الرياضية إلى برامج تعليمية متسلسلة تعتمد على "شفرة الحاسب" لاتخاذ القرارات المنطقية وإجراء العمليات الحسابية المعقدة بسرعة فائقة مقارنة بالآلات المكتبية التقليدية التي كانت مستخدمة في ذلك الوقت. كما يستعرض الملف التقنيات المادية المستخدمة في تلك الحقبة للتعامل مع البيانات، موضحاً آليات عمل أجهزة الإدخال والإخراج المختلفة مثل الأشرطة الورقية المثقبة والبطاقات المخرمة والأشرطة المغناطيسية، مع مقارنة بين أنواع وسائط التخزين من حيث السعة وسرعة الوصول والتكلفة. ويتعمق البحث في شرح الخصائص الفيزيائية للذاكرة المغناطيسية، سواء كانت تعتمد على الأسطوانات الدوارة أو الحلقات الفيرومغناطيسية المتناهية الصغر، مبيناً كيفية تسجيل واسترجاع المعلومات عبر النبضات الكهربائية والمجالات المغناطيسية، مما مهد الطريق لحل المشكلات العلمية والاقتصادية والهندسية المتكررة من خلال الأتمتة التي تضمن دقة النتائج النهائية وتوفر مئات السنين من العمل اليدوي This research paper, published by the National Planning Institute in 1964, addresses the fundamental principles of digital computers and how information is processed. It begins with a historical overview of the development of human computational abilities from ancient times to the invention of Arabic numerals and the concept of zero. It then explains the difference between digital computers, which rely on discrete values and binary logic (0 and 1), and standard computers. The paper focuses on the computer's structural framework, comprised of five main units: input, storage, control, calculation, and output. It provides a detailed explanation of how mathematical problems are transformed into sequential learning programs based on "computer code" to make logical decisions and perform complex calculations at a significantly faster speed than the traditional desktop computers used at the time . The report also reviews the physical technologies used in that era to handle data, explaining the mechanisms of various input and output devices such as perforated paper tapes, punched cards, and magnetic tapes, while comparing different types of storage media in terms of capacity, access speed, and cost. The research delves into the physical properties of magnetic memory, whether based on rotating disks or micro -ferromagnetic loops , demonstrating how information was recorded and retrieved via electrical pulses and magnetic fields. This paved the way for solving recurring scientific, economic, and engineering problems through automation , ensuring the accuracy of final results and saving hundreds of years of manual labor .